Coping with precarity: neoliberal global politics and female migration from Bulgaria to Greece (taking the lead from the case of Konstantina Kuneva) - Angelidou, Aliki (The Greek Review of Social Research, 2014)
Based on ethnographic study among Bulgarian women migrants in Athens and more particularly on the case of the attack against a Bulgarian cleaner and union representative Konstantina Kuneva, this article argues that female migration has to be understood as the consequence of the demise of the welfare state in former Eastern Europe and as resulting from the subsequent application of neoliberal politics. Most women migrate not only for making money but also to maintain their power and status as independent social actors and to negotiate unfavorable social positions and roles. However, the neoliberal restructuring of capitalist relations in the host country generates conditions of precarity for the migrants, especially for those working in the cleaning industry.